A ratiometric fluorescent sensor based on molecularly imprinted multilevel mesoporous silica for highly sensitive detection of imidacloprid. (December 2022) - Wei, Ziqi; Zhang, Weiyi; Wang, Shengjie; Han, Yiyi; Feng, Dongsheng; Ma, Yingqing; Deng, Bo; Chen, Zixin; Mao, Jialuo; Xu, Fei; Wang, Zhen; Cao, Hui
Abstract: Herein, A ratiometric fluorescent sensor based on molecularly imprinted multilevel mesoporous silica (MIFP—SiCQDs@CdTe QDs) was designed for highly sensitive detection of imidacloprid (IDP) pesticide with long half-life in soil, plants, and water environments. In this sensor, CdTe QDs were anchored onto the multilevel mesoporous of MIFP—SiCQDs by post-imprinting modification as the analytical signal to improve the detection sensitivity of the conventional doping method (d-MIFP). The results showed that the synthesized MIFP—SiCQDs@CdTe QDs possessed both small mesopore (2–3 nm) and large mesopore (5–50 nm), which is favorable for the anchoring of CdTe QDs (about 2–3 nm in diameter) and the mass transfer of IDP into them. Due to the multilevel mesoporous structure and low background, the sensor responded well to the addition of IDP in the range of 5 ng mL −1 –0.5 μg mL −1 with a detection limit of 3.55 ng mL −1 . The MIFP—SiCQDs@CdTe QDs sensor was successfully applied to determine IDP levels in real samples with the average recovery ranging from 97.64 to 109.88% and RSD values ranging from 1.00 to 4.65%. Furthermore, the quenching mechanism of MIFP—SiCQDs@CdTe QDs by IDP was considered to be the dynamic quenching. These results proved that the construction of multilevel mesoporous and post-imprinting modification of the analytical signal is an effective method to improve the sensitivity of d-MIP. Graphical abstract: Herein, A ratiometric fluorescent sensor based on molecularly imprinted multilevel mesoporous silica (MIFP—SiCQDs@CdTe QDs) was designed for highly sensitive detection of imidacloprid (IDP). The synthesized MIFP—SiCQDs@CdTe QDs possessed both small mesopore (2–3 nm) and large mesopore (5–50 nm), which is favorable for the anchor of CdTe QDs (about 2–3 nm in diameter) and the mass transfer of IDP into them. Image 1 Highlights: CQDs and CdTe QDs provided the built-in correction and the analytical signal, respectively. The synthesized MIFP—SiCQDs@CdTe QDs possessed both small mesopore and large mesopore. The sensing method has a high sensitivity for IDP with a LOD of 3.55 ng mL −1 and a wide linear range. The quenching mechanism of the sensor is dynamic quenching.